Lingual Thyroid Carcinoma: A Case Report and Review of Surgical Approaches in the Literature. (July 2018) - Stokes, William; Interval, Eric; Patel, Rusha
Introduction: Lingual thyroid cancer is a rare entity with a paucity of literature guiding methods of surgical treatment. Its location presents anatomic challenges with access and excision. Objective: We present a case of T4aN1b classical variant papillary thyroid carcinoma of the lingual thyroid that was removed without pharyngeal entry. We also present a review of the literature of this rare entity and propose a treatment algorithm to provide safe and oncologic outcomes. Findings: Our review of the literature found 28 case reports of lingual thyroid carcinoma that met search criteria. The trans-cervical/trans-hyoid approach was the most frequently used and provides safe oncologic outcomes. This was followed by the transoral approach and then lateral pharyngotomy. Complications reported across the series include 1 case of pharyngocutaneous fistula associated with mandibulotomy and postoperative respiratory distress requiring reintubation or emergent tracheostomy in 2 patients. Conclusion: The location of lingual thyroid carcinoma can be variable, and surgical management requires knowledge of adjacent involved structures to decrease the risk of dysphagia and airway compromise. In particular, for cases where there is extensive loss to swallowing mechanisms, laryngeal suspension can allow the patient to resume a normal diet after treatment.